The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1248/bpb.b16-00590
|View full text |Cite
|
Sign up to set email alerts
|

Differential Contribution of Nerve-Derived Noradrenaline to High K<sup>+</sup>-Induced Contraction Depending on Type of Artery

Abstract: High K -induced contraction of arterial smooth muscle is thought to be mediated by membrane depolarization and subsequent activation of voltage-dependent Ca 2 channels (VDCCs). In line with this, this study found that contraction induced by 80 mM K was almost abolished by nifedipine (1 µM), a VDCC inhibitor, in isolated rat aorta, and was markedly suppressed in the iliac artery. However, nifedipine (1 µM) only partially suppressed high K -induced contraction in the tail artery. The contractions remaining in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…It has been shown previously that SK&F 96365, another SOCE blocker, prevents contractions caused by cobra cardiotoxin [21]. The difference between the results of this study and ours may be explained by both the different specificity of the inhibitors [39] and the different cardiotoxin concentrations used. Further, we showed that ryanodine, the blocker of Ca 2 + release from SR, did not affect the magnitude of the cytotoxin effects at 10 µM; the contractions were equal 15 ± 6.4 and 30.4 ± 8.4% for CTX-1 and CTX-2, respectively (Figures 8b,g and 9b,g).…”
Section: Molecular Mechanisms Of the Aorta Rings Contractile Response...contrasting
confidence: 87%
“…It has been shown previously that SK&F 96365, another SOCE blocker, prevents contractions caused by cobra cardiotoxin [21]. The difference between the results of this study and ours may be explained by both the different specificity of the inhibitors [39] and the different cardiotoxin concentrations used. Further, we showed that ryanodine, the blocker of Ca 2 + release from SR, did not affect the magnitude of the cytotoxin effects at 10 µM; the contractions were equal 15 ± 6.4 and 30.4 ± 8.4% for CTX-1 and CTX-2, respectively (Figures 8b,g and 9b,g).…”
Section: Molecular Mechanisms Of the Aorta Rings Contractile Response...contrasting
confidence: 87%
“…Furthermore, it is known that high K + solution-elicited contraction is mainly related either to smooth muscle mass or to the function of voltage-dependent calcium channels in pulmonary vascular smooth muscle (Karaki et al, 1986;Ishida et al, 2017). SNP-mediated vasodilatation is related to signaling dependent on soluble guanylate cyclase (GC)-cGMPproduction-protein kinase G (PKG) signaling (Bilodeau-Goeseels, 2007).…”
Section: Discussionmentioning
confidence: 99%